THE MATHEMATICS BEHIND GEDUNG KEMBAR OF PURWAKARTA: TRACING GEOMETRIC TRANFORMATION - Bastianti, Artini; Aini, Indrie Noor (Prima: Jurnal Pendidikan Matematika, 2025)
The exploration of geometric transformations in Gedung Kembar of Purwakarta aims to explore the relationship between mathematical concepts and the architectural form of cultural heritage buildings in Purwakarta Regency. Qualitative methods were used to investigate the architectural elements of the building through direct observation. The focus of the study was on four main geometric transformations, namely translation, reflection, rotation and dilation, which were discussed in the context of building design and ornamentation. The results of the study show that the Purwakarta Twin Towers depict four types of geometric transformations (translation, reflection, rotation and dilation). The principle of translation can be seen in the repetition of neatly arranged pillar ornaments, while reflection can be seen in the identical and opposing shapes of the building ornaments, creating a symmetrical impression. The principle of rotation is found in the twin building ornaments, which depict the congruence of an object, but with a change in orientation. Dilation is seen in the difference in the size of the ornaments, one of which is found in the window ventilation, which emphasizes the artistic side. In general, this study shows that geometric transformations are not only abstract ideas in mathematics, but can also be applied in real life in architectural design. The Purwakarta Twin Buildings are a concrete example of how mathematical principles can be applied to physically beautiful forms. Thus, this exploration not only enriches our understanding of the relationship between mathematics and architecture, but also opens up learning opportunities relevant to the surrounding environment, which can be used in mathematics education in a local context